"Nonunion of Adult Humerus Fracture" - Management Using the Ilizarov External Fixator. - Das, Dilip Kumar; Paul, Arun Kanti; Datta, Dulal Chandra; Biswas, Debashis; Ahmed, SK Abdul Momen; Hashem, Muhammud Abu (Faridpur Medical College Journal, 2014)
Humeral shaft fractures occur about three percent of all fractures in adults. A very high union rate is achieved with non-operative treatment, however when nonunion occurs conservative approach or after operative management they are often very difficult to treat, and often requires multiple procedures to achieve union. Even with multiple procedures, true pseudoarthrosis have only a 59% union rate. The aim of this study was to find out the results of such complicated cases treating with Ilizarov's external fixator. We conducted a prospective study of eleven patients with nonunion humeral shaft fracture in adult wherein the outcome of the treatment was analyzed. In our series we achieved union in all of the cases with a mean of 29.1 weeks with negligible complications like pin tract infections and in one case refracture occur due to forceful manipulation. So it can be concluded that Ilizarov's method is an excellent option for the treatment of nonunion of diaphyseal fracture of the humerus. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20372 Faridpur Med. Coll. J. 2013;8(2): 67-72